PERKEMBANGAN ONTOLOGI DALAM FILSAFAT ISLAM - Fathul Mufid (LP2M IAIN kUDUS, 2013)
THE ONTOLOGY DEVELOPMENTS IN ISLAMIC PHILOSOPHY. The primary basis in the study of ontology is what it is, where it exists and, what the truth is. The fundamental and profound of these issues, so that people are faced with different answers. The first question, “what is there”, gives different answers according to their beliefs. Monism, which is only one and that one was spirit and ideas, then gave the flow of spiritualism and idealism. But if that one is full of material, then gave materialism. Dualism, that is round two, for example, body and soul, it gives the existentialism flow. Pluralism, that is composed of many elements, there is something that cannot be known, then gave the flow of agnosticism. The second problem, “where it exists”, the answer is that dwells in the world of ideas, abstract, fixed and immutable. That is living in the world of ideas that are concrete and individual, so that the truth is limited and changeable. The third issue, “what the truth is”, if the truth is eternal and immortal, then it is God. However, if the truth is capricious, then the problem is how to change it and what determines the change.Keywords: Ontology, Philosophy, Existence, Essence, Metaphysics.Dasar utama dalam kajian ontologi adalah apa yang ada, di mana yang ada dan, apa itu kebenaran. Sedemikian mendasar dan mendalamnya persoalan-persoalan ini, sehingga manusia dihadapkan pada jawaban-jawaban yang berbeda. Persoalan pertama, “apa yang ada”, memberikan jawaban yang berbeda-beda sesuai dengan keyakinan mereka. Monisme, yang ada hanya satu dan yang satu itu serba spirit dan ide, maka melahirkan aliran spiritualisme dan idealisme. Tetapi jika yang satu itu serba materi, maka melahirkan materialisme. Dualisme, yang ada serba dua, misalnya jiwa dan raga, maka lahirlah aliran eksistensialisme. Pluralisme, yang ada terdiri atas banyak unsur, yang ada adalah sesuatu yang tidak dapat diketahui, maka melahirkan aliran agnostisme. Persoalan kedua, “di mana yang ada”, jawabannya adalah yang bersemayam dalam dunia ide, bersifat abstrak, tetap, dan abadi. Yang ada bermukim di dunia ide yang bersifat kongkret dan individual, sehingga kebenarannya terbatas dan berubah-ubah. Persoalan ketiga, “apakah kebenaran itu”, jika yang dimaksud kebenara itu kekal dan abadi, maka itu adalah Tuhan. Akan tetapi, jika kebenarannya berubah-ubah, maka persoalannya adalah bagaimana perubahan itu dan apa yang menentukan perubahan itu.Kata Kunci: Ontologi, Filsafat, Ada, Hakikat, Metafisika.